Effect Of District On Carcass Traits And Bone Meat Ratio In Native Chicken - Gopinath, C.R.; Narasimhamurthy, H.N.; Nagarahalli, Rajakumar; Umakantha, B.; Nagaraja, C.S.; Isloor, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Indigenous chicken have their own importance, hence, a study was conducted to evaluate their carcass traits. Significant (P < 0.05) differences were noticed between the districts in per cent dressed and eviscerated weight traits. Significant ( P < 0.05 ) differences were noticed in blood, heart, gizzard and giblet per cent weight as well as cut up parts like, drumstick, thigh and neck per cent weight between the districts. The average Bone : Meat ratio recorded was 1: 3.53, 1: 3.54 and 1: 4.08 in birds of Chamarajanagar, Mysore and Mandya districts, respectively.
Keywords: Indigenous chicken. Carcass; Intensive system; Bone meat ratio